Perancangan Interior Garena E-Sports Stadium Di Surabaya - Yoshua Okinanta; Nyoman Adi Tiaga; Sherly De Yong (Intra, 2017)
Nowadays the development of gaming industry has made great progress, in this development of game industry there’s E-Sport which one of thie fastest growing fields, this can be seen since there is a lot of interests from youth people who are enthusiastic and plunge into E-Sports. However, the problem is there is no facilities that can contain the activity of E-Sports itself, purpose of this design is to create facilities that can contain E-Sports activity in Surabaya. Design method used is through Standford’s Design Thinking including Understanding , Emphatize , Define , Ideate , Prototype , Test and ended with implementation. By bringing Garena brand which is one of game publisher company in Indonesia, then implementation and brand recognition in this planning will be applied in a form of design as modern interior elements such as Hexagonal pattern, material that used also dominated by glossy material because it gives luxurious effect. This design also use colors Red,Black,and White which is the brand color from Garena itself. Writer expect a well-applied concept in this planning will become a facility that can accomodate and supportss E-Sports activity in Surabay